2020
DOI: 10.21203/rs.3.rs-56127/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Possible mechanisms of the hypoglycaemic effect of artesunate: Gender implication

Abstract: Background Artesunate is an antimalarial drug that affects glucose homeostasis but the mechanism of its glucose-modulating effect is not fully understood especially with gender implication, which is the information this study sought to provide. Methods Twenty-five (25) male and 25 female rats were separately and blindly allocated into five identical groups (n = 5/group). Group I (control) received 0.2 ml/kg distilled water. Groups II and III both received 2.90 mg/kg artesunate on day one, but 1.45 mg/kg from… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 37 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…Caffeine caused significant increased blood glucose level in normal and thyroidectomized rats of this study. This effect is in consonance with the well documented effect of acute caffeine exposure (Oyebola and Alada, 1993;Dekker et al, 2007;Salahdeen and Alada, 2009;Alagbonsi et al, 2016;Shi et al, 2016;Reis et al, 2018) on blood glucose in normal rats. Caffeine increases blood glucose through its stimulation of adrenal gland release of adrenaline (Battram et al, 2005), hence studies have linked acute caffeine consumption, increased plasma adrenaline and decreased insulin sensitivity (Dekker et al, 2007).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Caffeine caused significant increased blood glucose level in normal and thyroidectomized rats of this study. This effect is in consonance with the well documented effect of acute caffeine exposure (Oyebola and Alada, 1993;Dekker et al, 2007;Salahdeen and Alada, 2009;Alagbonsi et al, 2016;Shi et al, 2016;Reis et al, 2018) on blood glucose in normal rats. Caffeine increases blood glucose through its stimulation of adrenal gland release of adrenaline (Battram et al, 2005), hence studies have linked acute caffeine consumption, increased plasma adrenaline and decreased insulin sensitivity (Dekker et al, 2007).…”
Section: Discussionsupporting
confidence: 89%
“…The lack of total abolishment of the caffeine-induced increased blood glucose in the thyroidectomized rats of the current study may be linked with the interaction of caffeine with adenosine receptor, caffeine is a potent non-selective adenosine receptor antagonist and exerts most of its biological activities by blocking all types of adenosine receptors (Ribeiro and Sebastião, 2010). Agonist of adenosine receptors have been shown to decrease blood glucose and their blockade increases blood glucose (Alagbonsi et al, 2016) therefore, caffeine may utilize the adenosine receptor blockade pathway independently of its direct stimulation of adrenaline release to increase blood glucose level. Earlier reports have shown that adenosine receptor expression is greatly increased in hypothyroid rats (Baños et al, 2002) thus, their blood glucose lowering effect may be effectively blocked by caffeine administration in the thyroidectomized rats hence providing additional pathway for caffeine induction of high blood glucose level in the thyroidectomized rats.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…ART is metabolized to docosahexaenoic acid (DHA) as it enters the body (16)(17)(18). ART induces the generation of ROS, increasing malondialdehyde levels and decreasing the levels antioxidants such as superoxide dismutase and catalase, thereby causing alkylation of the proteins of the Plasmodium parasite (19). At present, ART is mainly used for the treatment of malaria of all types (20), for immune regulation (in type 1 diabetes in NOD mice) (21), as well as for liver (22), breast (23) and lung (24-26) cancer.…”
Section: Source and Activity Of Artmentioning
confidence: 99%